F1 Holstein x Zebu Cows in late pregnancy show physiological adaptation when raised in semiarid environment (Revista de Ciências Agroveterinárias, 2017)
This study aimed to verify the adaptability of F1 Holstein x Zebu cows in the late pregnancy third, raised in the semiarid region of Minas Gerais, by means of physiological responses. A total of ten cows were used, all in fourth pregnancy. To characterize the climatic environment, daily collections of air temperature, air relative humidity and wind speed were carried out to enable the calculation of the Globe Temperature and Humidity Index (GTHI) and Radiant Thermal Load (RTL). The physiological parameters analyzed were: respiratory frequency, rectal temperature and surface body temperature, at 10 am and 3 pm. The adaptability tests used were Heat Tolerance Index (HTI) and Heat Tolerance Coefficient (HTC). The climatic environment was out of thermal comfort in the afternoon. There were significant differences (P
Keywords: Family farming; Ambience; Dairy cattle; Heterosis.